2003
DOI: 10.1177/0037768603050001966
|View full text |Cite
|
Sign up to set email alerts
|

Discours Voilés Sur Les Musulmanes En Europe: Comment Les Musulmans Sont-ils Devenus Des Musulmanes?

Abstract: Islam has for a long time been perceived as a purely male religion. This is no longer the case nowadays in Europe. Various elements have helped the “feminization” of Islam in Europe, in particular at the level of its public reception. The veil affairs are among these. Political and scientific discourses have played a role in explaining that wearing the veil could be interpreted differently as the symbol of anti-modernity and backwardness. At the centre of this public dimension of veil affairs, a young woman po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The popularity of the headscarf among Muslim youth in Western-Europe (and the Middle East) can indeed equally be viewed as a reaction to secularist and neocolonial policies, and thus reduced to these power structures. This perspective has been adopted by scholars who have explained the popularity of the veil by pointing to the role of anti-colonial authenticity movements such as Islamist movements (Lazreg, 2009) or by viewing it as an affirmation of Muslim identity politics (Göle, 1993; Khosrokhavar, 1997; Roy, 2000; Amiraux, 2003). This perspective has, however, rightfully been challenged in its incapacity to account for the ethical agency of Muslim women and their references to the Muslim normative tradition (Mahmood, 2001).…”
Section: Not-veiling As An Aesthetic Of the Selfmentioning
confidence: 99%
“…The popularity of the headscarf among Muslim youth in Western-Europe (and the Middle East) can indeed equally be viewed as a reaction to secularist and neocolonial policies, and thus reduced to these power structures. This perspective has been adopted by scholars who have explained the popularity of the veil by pointing to the role of anti-colonial authenticity movements such as Islamist movements (Lazreg, 2009) or by viewing it as an affirmation of Muslim identity politics (Göle, 1993; Khosrokhavar, 1997; Roy, 2000; Amiraux, 2003). This perspective has, however, rightfully been challenged in its incapacity to account for the ethical agency of Muslim women and their references to the Muslim normative tradition (Mahmood, 2001).…”
Section: Not-veiling As An Aesthetic Of the Selfmentioning
confidence: 99%
“…Regardless of their criticism, many interlocutors, especially many German liberal feminists (both Muslim and non-Muslim), hewed to a narrow interpretation of women's oppression, rooted in colonial representations of postcolonial difference, with many seeing headscarfwearing women as victims of oppression (Taz, 23 July 2004;Taz, 19 October 2006;Taz, 20 August 2009). Some German Muslim women disrupted the connections made across anti-headscarf arguments, in which liberal feminism provides both a clear-cut analysis of the headscarf as oppressing women and a clear-cut solution, namely that it should be banned (see also Amiraux, 2003;Nyhagen, 2017). For example, Die Zeit reported that Saliha Kubilay, a young Muslim woman, asked Schwarzer during a public discussion at a university, 'Where in the feminist movement did you stop progressing so as to fail to grasp to this day that Islamic feminism has been long present in Germany?'…”
Section: Germanymentioning
confidence: 99%
“…Some studies have depicted how Islam could be harnessed for the control of MC women in British society within patriarchal family/community structures, particularly among socially disadvantaged strata (Macey, 1999). However, Islam can also be appropriated differently by educated women (Amiraux, 2003; Tietze, 2001).…”
Section: Islam Muslim Groupmentioning
confidence: 99%